Cardiovascular toxicity in testicular germ cell tumor survivors - Orszaghova, Zuzana; Mladosievicova, Beata; Mego, Michal; Chovanec, Michal (Frontiers in Oncology, 2025)
IntroductionTesticular germ cell tumors (TGCT) are highly curable malignancies, with excellent survival rates largely attributable to advances in cancer treatment. Consequently, there is a growing population of long-term TGCT survivors whose life expectancy approaches that of the general population. However, these survivors may experience acute and late adverse effects of cancer treatment, with cardiovascular toxicity being among the most serious and potentially life-threatening.MethodsThis narrative review synthesizes current evidence on cardiovascular toxicity in testicular cancer survivors, including clinical manifestations, pathophysiology of cisplatin-induced cardiovascular damage, additional adverse effects of radiotherapy, and prevalence of traditional cardiovascular risk factors. Key clinical guidelines, observational studies, and experimental findings were analyzed to identify trends, knowledge gaps, and opportunities for improving survivorship care.ResultsMultiple studies consistently demonstrate an increased risk of cardiovascular disease (CVD) among TGCT survivors, particularly following cisplatin-based chemotherapy. Common clinical manifestations include myocardial infarction, angina pectoris, cerebrovascular events, thromboembolism, and heart failure. The highest risk occurs within the first year post-treatment but may persist or recur even after a decade. Cisplatin-induced cardiovascular toxicity involves vascular injury - characterized by endothelial dysfunction, oxidative stress, and prothrombotic state - and myocardial damage driven by oxidative stress, inflammation, and apoptosis. Furthermore, TGCT survivors exhibit a higher prevalence of traditional cardiovascular risk factors, such as smoking, hypertension, dyslipidemia, diabetes, and obesity, contributing to the overall elevated CVD risk.DiscussionThere is an urgent need for a structured, long-term survivorship care model for TGCT survivors. Cardiovascular risk assessment and prevention should be central components, especially in survivors treated with cisplatin-based chemotherapy. Early detection of treatment-related toxicities, combined with lifestyle interventions and regular monitoring, is essential. Future research should focus on elucidating molecular mechanisms of cardiovascular toxicity, validating TGCT survivor-specific screening tools, identifying early biomarkers of cardiac injury, and exploring pharmacologic and behavioral interventions.ConclusionProtecting cardiovascular health in TGCT survivors requires a proactive, personalized, and multidisciplinary approach. Integrating cardiometabolic monitoring, risk factor modification, and tailored follow-up strategies into survivorship care is vital. Focused research and clinical attention are needed to ensure that the long-term success of cancer treatment is not compromised by preventable cardiovascular disease.